Objectivity is an Elusive Ideal that Can Never be Achieved - Ajjan, Mazen (Mediterranean Journal of Social Sciences, 2021)
The Paper investigates objectivity of Mass Media in the Middle East. The researcher chooses the most prominient news channel in that turbulent area of the world, namely Al-Jazeera Arabic news channel and examines its journey to claim its assumed objectivity. The paper gives analysis of objectivity in different cultureal contexts. It shows the ways Al-Jazeera established itself as an objective voice and how it presented itself as an alternative view to the dominant western perspective of global news. At the end the paper takes an intersting turn by bringing objectivity back to its "stallwart" – American journalism, where it was openly dropped in the face of national threat. The study realizes that the same conditions which gave Al-Jazeera Arabic its objectivity, in the eyes of its viewers, were the ones that its competitors used to disclaim its objectivity. Conditions can easily change if circumstances or attitudes changed. The paper concludes that Objectivity, in its bright side, is an elusive ideal that can never be achieved in our turbulant world. Received: 27 February 2021 / Accepted: 8 April 2021 / Published: 17 May 2021